DRIVE-THRU TRANSFORMATION: ELEVATING CUSTOMER SATISFACTION WITH DIGITAL TWINS - SURYAWIJAYA, TITO WIRA EKA; LANAWAANG, YEHUDA MARCEL; MAHMUD, MAHMUD; KHANT, THANT THET OO (Jurnal Manajemen dan Dinamika Bisnis (JMDB), 2024)
In the modern business landscape, traditional methods of understanding consumer behavior are constrained by time, cost, and depth limitations. The emergence of Digital Twins, which are virtual replicas created through real-time data integration and advanced algorithms, has fundamentally transformed how we perceive consumer behavior and market responses. This study aims to address challenges related to data security and privacy, exploring potential solutions within the context of applying Digital Twins in drive-thru services. Using a quantitative approach with a sample size of 2000 American drive-thru service customers, the research employs SEM-PLS for data analysis. Online questionnaires are distributed through Triaba to collect targeted data. The findings indicate that while process efficiency in drive-thru services has little impact on service quality, Digital Twins can still lead to waiting times that challenge customer expectations. Although limited to America, this research confirms the significant role of Digital Twins in enhancing drive-thru service efficiency and customer satisfaction, providing valuable insights for users and system integrators during implementation.